Epistemologi Hadis Ḍa‘īf Dan Mauḍū‘ : Perspektif Filsafat Ilmu - Abdul Jabbar Mukhtar; Rohanda Rohanda; Abdul Kodir (Institut Muslim Cendekia, 2026)
This study investigates ḍa‘īf (weak) and mauḍū‘ (fabricated) ḥadīṡ by integrating classical ḥadīṡ sciences (‘ulūm al-ḥadīṡ) with the perspective of the philosophy of science. The research is motivated by the concern over the prevalent use of ḍa‘īf and mauḍū‘ ḥadīṡ among muslims, particularly in religious activities. Employing a qualitative library research method, this study analyzes primary data consisting of classical texts on ḍa‘īf and mauḍū‘ ḥadīṡ, alongside secondary data covering epistemology and modern philosophy of science literature. The findings reveal a significant distinction between ḍa‘īf and mauḍū‘ ḥadīṡ from both ḥadīṡ science and epistemological perspectives, despite their shared failure to meet the requirements of authenticity (ṣahīh). Ḍa‘īf ḥadīṡ retains an empirical existence within the transmission chain that can be traced through the science of narrators (rijāl al-ḥadīṡ) and offers spiritual utility, albeit limited to virtuous deeds (faḍāīl al-a’māl). In contrast, mauḍū‘ ḥadīṡ is categorized as pseudo-knowledge or false information that threatens the purity of Islamic teachings.